Structure of Methanobactin SB2 May Help Define a Whole New Class of Peptide-derived Metal-binding Molecules - Krentz, Benjamin (My University, 2010)
Methanobactins are peptide-derived, copper-binding molecules produced by mathanotrophic bacteria that use methane as their primary source of carbon and energy. They synthesize methanobactin to scavenge copper ions from the environment and use this copper as a cofactor for the enzyme that catalyzes the conversion of methane to methanol. Here we report our results for determining the chemical structure of a new form of mehtanobactin, methanobactin SB2, and compare this structure to a previously determined structure for another methanobactin, methanobactin O3b3.
Structure of a New Methanobactin Hints at the Existence of a Whole New Class of Peptide-derived Metal-binding Molecules
Color poster with text and diagrams.
Keywords: Methanobactin; Peptides--Structure; Posters